Activity of catalase ferment of mandarin leaves in the subtropics of Russia - J. S. Abilfazova (Новые технологии, 2017)
The article presents the results of long-term studies of 6 varieties and 2 hybrids of Citrus unshiu: Miagawa-Vase (St.); Vavilov’s Glory; Jubilee; September; Kodorsky; Unshiu; 16939 Hybrid (Miagawa-Vase x Natsu Mikan); 16954 Hybrid (Miagawa-Vase x Yuka), growing in the subtropical zone of the Krasnodar Territory, characterized by high catalase enzyme activity and resistance to changes in soil-climatic conditions.